Length of Stay Beyond Medical Readiness: A Follow-up, Prospective Cohort Analysis. (16th November 2020) - Linzey, Joseph R; Foshee, Rachel; Moriguchi, Francine; Adapa, Arjun R; Koduri, Sravanthi; Kahn, Elyne N; Sheehan, Kyle; Rajajee, Venkatakrishna; Pandey, Aditya S
Abstract: INTRODUCTION: There is significant pressure on neurosurgeons to provide cost-effective healthcare and discharge patients once they are medically fit. Given a number of factors, it is not uncommon for patients to stay in the hospital beyond medical readiness (BMR). METHODS: We performed a prospective, cohort analysis of all admitted neurosurgical patients to our institution. The length of stay (LOS) BMR was assessed daily by the attending neurosurgeon and neuro-intensivist with a standardized criterion. Univariate and multivariate logistic regressions were performed. RESULTS: Of the 884 patients, 229 (25.9%) had a LOS-BMR. Patients with a LOS-BMR were significantly more likely to be older (61.5 ± 14.0 vs 57.3 ± 15.1, P  = .0002), have hemiplegia (5.7% vs. 1.2%, P  = .001), have dementia (2.2% vs. 0.2%, P  = .005), have liver disease (6.6% vs. 3.4%, P  = .04), have renal disease (14.4% vs. 9.5%, P  = .04), and have diabetes mellitus (23.1% vs. 16.6%, P  = .03). Patients with a LOS-BMR were significantly more likely to be discharged to subacute rehabilitation/skilled nursing facility (40.2% vs 4.1%) or an acute/inpatient rehabilitation facility (22.7% vs. 1.7%, P  < .0001). After multivariate logistic regression, patients with a LOS-BMR were almost 4 times more likely to have a consult to PT placed during their hospital admission (OR 3.82, 95% CI 1.94-7.55, P  = .0001). Patients who were discharged to subacute rehabilitation/skilled nursing facilities (OR 12.11, 95% CI 6.18-23.72, P  < .0001) or acute/inpatient rehabilitation facilities (OR 11.09, 95% CI 4.90-25.08, P  < .0001) were significantly more likely to have a LOS-BMR. The average LOS-BMR was 2.7 ± 3.1 days. During those days beyond medical readiness, the average cost was $9, 148.28 ± $12, 983.10 per day. In the 884 patients, the total cost incurred during the "beyond medical readiness" period was $2, 076, 659.32. CONCLUSION: A quarter of admitted neurosurgical patients remained in the hospital after they were medically ready for discharge, costing over $2, 000, 000.